Quantification of Orbital Apex Crowding for Screening of Dysthyroid Optic Neuropathy Using Multidetector CT - Gonçalves, A.C.P.; Silva, L.N.; Gebrim, E.M.M.S.; Monteiro, M.L.R. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: DON, a serious complication of GO, is frequently difficult to diagnose clinically in its early stages because of confounding signs and symptoms of congestive orbitopathy. We evaluated the ability of square area measurements of orbital apex crowding, calculated with MDCT, to detect DON. MATERIALS AND METHODS: Fifty-six patients with GO were studied prospectively with complete neuro-ophthalmologic examination and MDCT scanning. Square measurements were taken from coronal sections 12 mm, 18 mm, and 24 mm from the interzygomatic line. The ratio between the extraocular muscle area and the orbital bone area was used as a CI. Intracranial fat prolapse through the superior orbital fissure was recorded as present or absent. Severity of optic nerve crowding was also subjectively graded on coronal images. Orbits were divided into 2 groups (with or without clinical evidence of DON) and compared. RESULTS: Ninety-five orbits (36 with and 59 without DON) were studied. The CIs at all 3 levels and the subjective crowding score were significantly greater in orbits with DON (P < .001). No significant difference was observed regarding intracranial fat prolapse (P = .105). The area under the ROC curves was 0.91, 0.93, and 0.87 for CIs at 12, 18, and 24 mm, respectively. The best performance was at 18 mm, where a cutoff value of 57.5% corresponded to 91.7% sensitivity, 89.8% specificity, and an odds ratio of 97.2 for detecting DON. A significant correlation (P < .001) between the CIs and VF defects was observed. CONCLUSIONS: Orbital CIs based on area measurements were found to predict DON more reliably than subjective grading of orbital crowding or intracranial fat prolapse. CIcrowding indexDONdysthyroid optic neuropathyGOGraves orbitopathyHUHounsfield unitMDCTmultidetector CTROCreceiver operating characteristicSAPstandard automated perimetryVAvisual acuityVFvisual fieldWLwindow levelWWwindow width